Analisis Problem Solving Pada Hadis Kontradiktif - Fadhilah Is (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
Hadith is the second source of tasyri' after the Qur'an. Hadith functions as bayan at-taqrir, bayan at-tafsir, bayan at-tasyri' . In musthalah hadith , the term mukhtalif hadith is known, namely two maqbul hadiths that contradict each other outwardly, have the same position, which can be used as evidence . Problem solving against the contradictions of this hadith by means of jam'u , tarjih, nasakh or tawaqquf. The cause of the emergence of this contradictory hadith is the existence of internal factors, external factors, methodological factors, and ideological factors . This journal discusses the causes of hadith contradictions and problem solving against mukhtalaf hadith . The result is that contradictory hadiths of the Prophet are only outwardly, the scholars have made ijtihad to resolve them even though there are differences of opinion between them.